Efektivitas Pelatihan Dasar CorelDRAW dalam Meningkatkan Keterampilan Desain Grafis OSIS SMKN 1 Arjasa - Ahmad Afandi; Ahmad Tahqiq Rofiq; Zaehol Fatah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Basic CorelDRAW training aimed to improve vector-based graphic design skills for OSIS students at SMKN 1 Arjasa. This activity was motivated by students' low proficiency with design software and their reliance on external parties for the creation of organizational promotional media. The training was conducted over two days using an active learning approach through interactive lectures, demonstrations, group discussions, and hands-on practice, involving 18 participants from active OSIS members. This activity was also supported by the OSIS advisor and the school as partners in the implementation. Evaluation results showed a 35% increase in participants' technical skills based on pre- and post-training scores, as well as increased confidence in producing pamphlets and posters independently. This activity not only supported OSIS operational efficiency but also equipped students with essential competencies in the digital technology-based workplace. This training is the first step in developing a digital skills strengthening program for the era of Industry 4.0 and Society 5.0.